PENGARUH KEMAMPUAN INTELEKTUAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Damanik, Bahrudi Efendi (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Abstract: The formulation of this research problem is how the influence of intellectual ability on teacher performance, how the influence of work motivation on teacher performance, how the influence of intellectual ability and work motivation on teacher performance. The purpose of this study is to determine the effect of intellectual ability on teacher performance, to determine the effect of work motivation on teacher performance, to determine the effect of intellectual ability and work motivation on teacher performance. With multiple linear regression analysis techniques obtained the following research results. Intellectual ability and motivation variables simultaneously have positive and significant effect on teacher performance with Fcount> Ftable (17.906> 3,350). Partial intellectual ability variable has positive and significant effect on teacher performance, with tcount> ttable (2,339> 2,042). Partial motivation variable has positive and significant effect on teacher performance with tcount> ttable (5,552> 2,042). The value of R Square in the above table is 0,570, it shows that 57 % variable of teacher performance can be explained by intellectual ability and motivation variable, while the rest of 43% is explained by other un-researched variables such as teacher discipline level, teacher competency, PBM and so forth.